PENENTUAN KESESUAIAN LAHAN UNTUK TANAMAN CABAI MERAH DI PULAU REMPANG MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Sudra Irawan; Andi (ABEC Indonesia, 2021)
The growth of red chili pepper does not depend on the season but is influenced by environmental characteristics. The purpose of this study is to determine the level of land suitability for red chili pepper plants in Rempang Island based on its physical characteristics by utilizing Geographic Information System (GIS) technology. The method adopted is the evaluation of land suitability, by comparing the characteristics of the land with the criteria for growing red chili pepper plants in each SPL (Satuan Peta Lahan, Land Map Unit). The results obtained from this study are actual land suitability and potential land suitability within 4 classes: S1 (very suitable), S2 (fairly suitable), S3 (marginally suitable), and N (not suitable). 8,946.82 hectares of actual land are in the S3 class with limiting factors including nutrient retention, water availability, and erosion hazard. 3,225.27 hectares of land are in class N with limiting factors consisting of erosion hazard and temperature. On potential land, 7,993.56 hectares of land in SPL 1, 3, 4, 5, and 6 are in the S2 class with limiting factors including erosion hazard, temperature, and oxygen availability. 4088.50 hectares of land in SPL 2 is in the S1 class and has no limiting factor. Efforts to increase the suitability can be carried out on the land with limiting factors such as water availability, nutrient retention, and erosion hazard. However, on limiting factors such as temperature, no effort can be made.